Effects on extraction time, temperature and agitation on antioxidant activity of curcuma xanthorrizza - Sarmidi, Mohd. Roji (2007)
Naturally occurring phytochemicals with antioxidant properties are widely used in food industry. Antioxidant activities of Curcuma xanthorrizza are mainly attributed by a group of polyphenolic compound known as curcuminoid. The curcuminoids ae contained in the oleoresin cells. Extraction of oleoresin involves several processing parameters that can alter the nutritional and chemical properties of raw materials. Optimum responses obtained from optimization process were 3.8% (w/) for oleoresin, 13.3% curcumin content and 77.2% antioxidant activity.